Uprość wyrażenia dzk

Uprość Wyrażenia Dzk class=

Odpowiedź :

Odpowiedź:

[tex]a)\\\\x-2y(3x+5)-4xy=x-6xy-10y-4xy=x-10xy-10y\\\\(3x-2)(4x+5)+2x(x+3y)=12x^2+15x-8x-10+2x^2+6xy=\\\\=14x^2+7x+6xy-10\\\\\\b)\\\\3a-(2a-1)(4b-3)+5=3a-(8ab-6a-4b+3)+5=3a-8ab+6a+4b-3+5=\\\\=9a-8ab+4b+2\\\\-3(5-3a)-(4b-2c)+\frac{1}{4}(a-c)=-15+9a-4b+2c+\frac{1}{4}a-\frac{1}{4}c=\\\\=9\frac{1}{4}a-4b+1\frac{3}{4}c-15[/tex]

[tex]c)\\\\2x(3x+5)(4y-6)-2(x+3y)=(6x^2+10x)(4y-6)-2x-6y=\\\\=24x^2y-36x^2+40xy-60x-2x-6y=24x^2y-36x^2+40xy-62x-6y\\\\\\\frac{x-2y}{3}+\frac{3x+y}{2}-5(x-2y)=\frac{x-2y}{3}+\frac{3x+y}{2}-5x+10y=\frac{2(x-2y)}{6}+\frac{3(3x+y)}{6}-\frac{6(5x+10y)}{6}=\\\\=\frac{2x-4y}{6}+\frac{9x+3y}{6}-\frac{30x+60y}{6}=-\frac{19}{6}x+\frac{59}{6}y[/tex]